2014
DOI: 10.1002/pat.3415
|View full text |Cite
|
Sign up to set email alerts
|

Use of maleic anhydride compatibilization to improve toughness and other properties of polylactide blended with thermoplastic elastomers

Abstract: Polylactide (PLA) being a very brittle biopolymer could be toughened by blending with thermoplastic elastomers such as thermoplastic polyurethane elastomer (TPU) and thermoplastic polyester elastomer (TPE); unfortunately, these blends are immiscible forming round domains in the PLA matrix. Therefore, the purpose of this study was to investigate the effects of using maleic anhydride (MA) compatibilization on the toughness and other properties of PLA blended with TPU and TPE. MA grafting on the PLA backbone (PLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 35 publications
7
45
1
Order By: Relevance
“…Among the three ternary blends prepared at different temperatures, the d w value is unexpectedly the largest for the one at 240 °C with the strongest interfacial adhesion and its particle size distribution also appears the narrowest. This result is evidently different from those of the previously reported rubber‐toughened PLA blend systems only involving reactive compatibilization, in which the improved interfacial adhesion is usually accompanied by a decrease in the dispersed particle size and its distribution due to the emulsifying role of the in situ formed copolymer . The aforesaid difference could be attributed to the unique characteristics of the PLA/EBA‐GMA/EMAA‐Mg blend system investigated in this work, which is simultaneous occurrence of interfacial compatibilization and crosslinking reactions both associated with rubbery EBA‐GMA phase.…”
Section: Resultscontrasting
confidence: 96%
“…Among the three ternary blends prepared at different temperatures, the d w value is unexpectedly the largest for the one at 240 °C with the strongest interfacial adhesion and its particle size distribution also appears the narrowest. This result is evidently different from those of the previously reported rubber‐toughened PLA blend systems only involving reactive compatibilization, in which the improved interfacial adhesion is usually accompanied by a decrease in the dispersed particle size and its distribution due to the emulsifying role of the in situ formed copolymer . The aforesaid difference could be attributed to the unique characteristics of the PLA/EBA‐GMA/EMAA‐Mg blend system investigated in this work, which is simultaneous occurrence of interfacial compatibilization and crosslinking reactions both associated with rubbery EBA‐GMA phase.…”
Section: Resultscontrasting
confidence: 96%
“…The micrographs for the neat PLA and TPU exhibit a smooth surface; however, the dimples are observed in the PLA/TPU blends. Furthermore, unclear morphology of the two phases is evident in the blends SEMs, which further proves that PLA was partially miscible with TPU due to the high interfacial interactions . In PT7030 sample, a large contribution of the TPU spheres were uniformly suspended in the PLA matrix, it is also shown that TPU particles are started to join together leading to the continuous morphology.…”
Section: Resultsmentioning
confidence: 88%
“…According to technical data sheet density of this PLA is 1.25 g/cm 3 . Its molecular weight was measured as 980000 in our previous study [27]. Polyvinylpyrrolidone (PVP) (Mw ¼ 55000), ethylene glycol (EG), silver nitrite (AgNO 3 ), sodium chloride (NaCl, 99.5%) were used for the Ag NW synthesis.…”
Section: Methodsmentioning
confidence: 99%